Penerapan Media Pembelajaran Power Point Interaktif guna Meningkatkan Keaktifan Peserta Didik - Nuraini Salam; Junaidi Junaidi (Naradidik: Journal of Education and Pedagogy, 2022)
This research is motivated by the problem of the lack of activity of students in class XI IPS 4 SMA Pertiwi 1 Padang in learning sociology, to overcome these problems, the application of interactive power point learning media is carried out, using classroom action research. Classroom action research method with a research design from Stephen Kemmis and Robbin MC Taggart conducted on students of class XI IPS 4 SMA Pertiwi 1 Padang. This study aims to increase the activeness of students in class XI IPS 4 at SMA Pertiwi 1 Padang in learning sociology by using interactive power point learning media. This research was conducted on students of class XI IPS 4 with a total of 26 students. Data collection techniques in this study are observation and interviews with qualitative data analysis techniques from interviews and quantitative data analysis techniques from observations. The results showed an increase in student activity, this can be seen from the observation sheet observed in the initial conditions or pre-action student activity the average was 19.22% and the first cycle the average student activity was 53.74% there was an increase in the difference of 44.52%, then the average student activity in the second cycle is 76.09%, the difference between the increase in the first cycle and the second cycle is 22.35%. This research ends in cycle II. It can be concluded that the application of interactive power point can increase student activity in learning sociology.